THERMOGRAVIMETRIC ANALYSIS MICROPARTICLES PEQUI OIL (CARYOCAR CORIACEUM WITTM.) IN A POLYMERIC MATRIX OF ALGINATE AND CHITOSAN - Castelo, Rachel Menezes; Silva, Luana Carvalho da; Alexandre, Joana de Barros; Freire, Gabrielle Albuquerque; Barroso, Tiago Linhares Cruz Tabosa; Furtado, Roselayne Ferro (Revista Coleta Científica, 2020)
Pequi oil has high level of antioxidant substances, phenolic compounds, vitamin A and E, substances that are sensitive to the presence of light and oxygen. In order to provide greater stability to these compounds, microencapsulation techniques have been applied. Microparticles have different characteristics depending on the matrix, the microencapsulation technique and the drying method used. Thermal stability of the resulting microparticles is always important for industrial applications. The objective of this work was to perform thermogravimetric analysis (TGA) of pequi oil microparticles (OP) with chitosan (QT) / alginate (AG) and alginate matrixes submitted to oven drying and freeze drying. The percentage weight loss was calculated over time. The QT/ AG/OP microcapsules showed a higher temperature and enthalpy of degradation than AG/OP, thus the electrolytic complexation of QT/AG resulted in better thermal stability. Regardless of the drying method applied, the QT/ AG/OP particles showed the first degradation peak at 375 ° C, thus this matrix was suitable for oil protection in terms of thermal resistance.